Molecular evidence for the efficacy of PBM therapy in the treatment of oral lichen planus - Maria Zaharieva Mutafchieva; Milena Nenkova Draganova; Plamen Ivanov Zagorchev; Reem Hanna; Georgi Tomchev Tomov (Photodiagnosis and Photodynamic Therapy)
Purpose: Oral lichen planus (OLP) is a chronic inflammatory disease, in which T-Lymphocytes induce apoptosis of basal keratinocytes, leading to the formation of symptomatic lesions. It is assumed that blocking the cell death program and enhancing cell proliferation would be crucial to the healing process. The aim of the study was to verify the efficacy of Photobiomodulation (PBM) in OLP management, by evaluating the effects of laser irradiation on the processes of apoptosis and cell proliferation. Methods: Twenty patients with OLP underwent PBM with 810 nm diode laser (0.5 W, 30 s, 1.2 J/cm2), 3 times a week for one month. The size and clinical scores of the lesions and pain level were recorded and compared before and after therapy using Thongprasom sign scoring system and Visual Analogue Scale, respectively. Biopsies were taken before and after therapy and analyzed immunohistochemically for bcl-2 and Ki-67 expression. Tissue sections from 10 healthy volunteers were used as controls for the levels of these markers in normal oral mucosa. Results: PBM significantly reduced patients’ pain intesity and improved the clinical signs of the lesions. OLP tissue sections demonstrated lower staining for bcl-2 and Ki-67 compared to healthy controls. After therapy the expression of bcl-2 increased significantly. An enhance in Ki-67 immunoreactivity was revealed predominantly in the atrophic-erosive epithelium. Conclusion: PBM is an effective treatment modality for OLP patients. Erosive forms of the disease responded better to laser irradiation than keratotic subtypes. At the molecular level, PBM is likely to recover the impaired cell cycle mechanisms and keratinocyte proliferation.